Terrorist learning in context – the case of Al Qaeda in the Islamic Maghreb. Issue 4 (2nd October 2019) - Goerzig, Carolin
ABSTRACT: It is astonishing how many researchers adopt a counterterrorism agenda and suggest researching terrorist learning in order to shape security countermeasures. Posing different questions would lead to different answers. One such question would be, "What makes terrorist learning different?" Terrorist groups operate clandestinely, which means the environment in which they learn is different. This paper investigates the context in which Al Qaeda in the Islamic Maghreb (AQIM) has learned. Thus, a qualitative case study analysis of the influence of meso- and macro-level factors on AQIM's tactical and strategic patterns between 1999 and 2013 will shed light on terrorist learning. Meso-level influences are conceptualised as cooperation and ultimate merging with Al Qaeda, and macro-level influences as government action. The result is puzzling: AQIM has learned tactically from Al Qaeda and strategically from counterterrorism. This is puzzling because scholars commonly question whether it is possible to learn under pressure. Nevertheless, AQIM's learning has been more profound when faced with pressure than when cooperating voluntarily. The sustainable answer to the question of the political implication thereof is not how to boost counterterrorism measures but how to redefine them. If what is different about terrorist learning is above all the context, we need to question the context.